Outcomes of persistent pulmonary hypertension following transcatheter aortic valve replacement. Issue 10 (29th September 2017) - Masri, Ahmad; Abdelkarim, Islam; Sharbaugh, Michael S; Althouse, Andrew D; Xu, Jeffrey; Han, Wei; Chan, Stephen Y; Katz, William E; Crock, Frederick W; Harinstein, Matthew E; Kliner, Dustin E; Navid, Forozan; et al.
Abstract : Objectives: To determine the prevalence and factors associated with persistent pulmonary hypertension (PH) following transcatheter aortic valve replacement (TAVR) and its relationship with long-term mortality. Methods: Consecutive patients who underwent TAVR from July 2011 through January 2016 were studied. The prevalence of baseline PH (mean pulmonary artery pressure ≥25 mm Hg on right heart catheterisation) and the prevalence and the predictors of persistent≥moderate PH (pulmonary artery systolic pressure (PASP)>45 mm Hg on 1 month post-TAVR transthoracic Doppler echocardiography) were collected. Cox models quantified the effect of persistent PH on subsequent mortality while adjusting for confounders. Results: Of the 407 TAVR patients, 273 (67%) had PH at baseline. Of these, 102 (25%) had persistent≥moderate PH. Mortality at 2 years in patients with no baseline PH versus those with PH improvement (follow-up PASP≤45 mm Hg) versus those with persistent≥moderate PH was 15.4%, 16.6% and 31.3%, respectively (p=0.049). After adjusting for Society of Thoracic Surgeons Predicted Risk of Mortality and baseline right ventricular function (using tricuspid annular plane systolic excursion), persistent≥moderate PH remained associated with all-cause mortality (HR=1.82, 95% CI 1.06 to 3.12, p=0.03). Baseline characteristics associated with increased likelihood of persistent≥moderate PH were ≥moderate tricuspid regurgitation, ≥moderate mitral regurgitation, atrial fibrillation/flutter, early (E) to late (A) ventricular filling velocities (E/A ratio) and left atrial volume index. Conclusions: Persistency of even moderate or greater PH at 1 month post-TAVR is common and associated with higher all-cause mortality.